Designing Health Education Model Overcoming Dating Violence for High School Students - Aprianti, Aprianti; Wulandari, Respati; Muthoharoh, Nor Amalia; Sifai, Izzatul Alifah; Azzahra, Fatimah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: The Women's Empowerment and Child Protection Service reported that there were 227 cases of Violence Against Women and Children in Semarang City in 2023, with the most victims being women at 216 people. The highest number of cases of violence occurred at the high school level, with 83 victims. The high number of cases of violence in dating requires prevention efforts. This study aims to design a health education model to address dating violence among high school students in Semarang City.Method: The type of research used is research and development. The P-Process theory is used as material for developing health promotion media. Qualitative and quantitative data sources were obtained in the research and development process. The stages of the research are situation analysis, which is conducted by quantitative research on 118 high school students in Semarang City, and purposive sampling techniques. Quantitative research with focus group discussion was conducted on 10 male and 10 female high school students, and in-depth interviews were conducted with 3 counseling teachers. Quantitative data analysis with the chi-square test, qualitative analysis with thematic content analysis.Result: The average age of respondents was 16 years, with the majority being female. The violence experienced by men was physical violence, while for women, it was psychological and sexual violence. There was a significant relationship between efficacy and self-efficacy responses to overcome violence in dating. For media development, most respondents preferred audiovisual media in the form of films with facilitators being peer educators; the maximum education time was 30 minutes, with materials covering adolescent development, how to overcome violence in dating, healthy dating, and the flow of complaints of violence in dating.